Investigation of the Effects of Rotor Pole Geometry and Permanent - Tarımer, İlhan (Elektronika ir Elektrotechnika, 2009)
The effects of rotor pole geometry to line start permanent magnet synchronous motor’s efficiency are discussed. To achieve this goal, several LSPMSMs which have eight type rotors and 550 Watts power have been simulated and analyzed. It has inferred that inset magnet and interior magnet rotor types provided higher efficiency and maximum permanent flux density on surface of rotor. Changing of permanent magnets’ material to NdFe35 raises motor’s efficiency. As result, the use of inset magnet and interior magnet rotor types and magnet’s material NdFe35 in LSPMSMs provide high efficiency and power density. It is suggested that SmCo28 material must be used on permanent magnet’s surfaces in high operating temperatures for powerful LSPMSMs. Ill. 9, bibl. 16 (in English; summaries in English, Russian and Lithuanian).